2012
DOI: 10.1371/journal.ppat.1002645
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T-Cells Expressing Interferon Gamma or Perforin Play Antagonistic Roles in Heart Injury in Experimental Trypanosoma Cruzi-Elicited Cardiomyopathy

Abstract: In Chagas disease, CD8+ T-cells are critical for the control of Trypanosoma cruzi during acute infection. Conversely, CD8+ T-cell accumulation in the myocardium during chronic infection may cause tissue injury leading to chronic chagasic cardiomyopathy (CCC). Here we explored the role of CD8+ T-cells in T. cruzi-elicited heart injury in C57BL/6 mice infected with the Colombian strain. Cardiomyocyte lesion evaluated by creatine kinase-MB isoenzyme activity levels in the serum and electrical abnormalities reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
230
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(257 citation statements)
references
References 44 publications
22
230
0
5
Order By: Relevance
“…Specific mechanisms regulating the effects of T cells in the heart during MAV-1 myocarditis have not yet been defined. CD8 ϩ T cells may play both inflammatory and cytolytic roles during infection, either by secretion of cytokines, such as IFN-␥ or TNF-␣, or through release of cytolytic granules such as Pfn (41). Both type I and type II IFN can play protective roles in other models of viral myocarditis (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific mechanisms regulating the effects of T cells in the heart during MAV-1 myocarditis have not yet been defined. CD8 ϩ T cells may play both inflammatory and cytolytic roles during infection, either by secretion of cytokines, such as IFN-␥ or TNF-␣, or through release of cytolytic granules such as Pfn (41). Both type I and type II IFN can play protective roles in other models of viral myocarditis (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Both type I and type II IFN can play protective roles in other models of viral myocarditis (12)(13)(14). IFN-␥ and Pfn play antagonistic roles during chronic myocarditis caused by Trypanosoma cruzi, with Pfn ϩ CD8 ϩ T cells implicated in causing tissue damage and IFN-␥ ϩ CD8 ϩ T cells preventing tissue damage (41). In the current study, we identified robust induction of IFN-␥ in the heart after MAV-1 infection, consistent with previous studies showing induction of IFN-␥ in MAV-1-infected lungs (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the severity of the disease, that is, tissue damage, resulting from Leishmania braziliensis infection is directly correlated with more granzymeproducing CD8 + T cells (76) and that CD8 + T cell-mediated cytotoxicity promotes lesions in cutaneous leishmaniasis (77). In addition, CD8 + T cells producing perforin might play a detrimental role in experimental T. cruzi infection in mice, leading to heart injury (78). Hence the infection severity in CCP might be associated with the increased frequency of CD8 + T cells with potent cytotoxic profiles corroborated by the high amount of granzyme B produced by the CD8 + T cells from patients classified as group D (Supplemental Fig.…”
Section: Cd8mentioning
confidence: 99%
“…These lymphocytes produce perforin, but not IFN- γ , and have a greater propensity to migrate to the heart tissue, causing tissue damage leading to CCC [85]. …”
Section: Role Of Cd8+ T Cells During T Cruzi Infectionmentioning
confidence: 99%